Characterization of a polymorphic immunodominant molecule in sporozoites and schizonts of Theileria parva - Toye, Philip G.; Goddeeris, M.; Iams, K.P.; Musoke, A.J.; Morrison, W. Ivan (Wiley, 1991)
Summary This study examines several aspects of a polymorphic, immunodominant molecule (P!M) found in the protozoan parasite. Theileria parva. The antigen is present in all T. p. parva stocks examined, and in the related subspecies, T. p. bovis and T. p. lawrencei. It is the predominant antigen recognized by antisera from immune cattle on Western blot analysis of schizont‐infected lymphocytes, and is the only antigen which has been shown to react with anti‐schizont monoclonal antibodies (MoAbs) on Western blots or in immunoprecipitations. The antigen shows polymorphism in both size and expression of antibody epitopes among the different stocks of T. parva. The antigen is present in sporozoites as well as schizonts.